Students’ Perceptions on the Use of PowerPoint Presentation as Learning Media in EFL Classroom - Yuliani, Sri; Sulaiman, Masagus; Dirgantara, Erwan; Restania, Mela (International Journal of Language Teaching and Education, 2021)
The objective of this study was to know the second semester students’ perceptions on the use of PowerPoint in EFL classroom. The researchers used a qualitative method in this study, and the sample of this study was the second semester students at English Education Study Program Universitas Muhammadiyah Palembang. The researcher collected the data by using questionnaire and analyzed the data by using percentage analysis. There were five questions out of twenty statements, such as agree, strongly agree, rarely, disagree, and strongly disagree. The results showed there were 80% questions that the students dominantly chose “agree”, 15% questions to “rarely”, and the “disagree” point had the highest percentage (21.43%) in the item “students prefer lesson without PowerPoint”. In addition, there were 69.05% students dominantly responded ‘agree’ that PowerPoint can gain their English skills. It means that the second semester students had positive opinions and perceptions about the use of PowerPoint presentation as learning media in EFL classroom.